Genetic and physiological studies of Bacillus subtilis sigma A mutants defective in promoter melting. - Rong, J C (1994)
The Bacillus subtilis sigA gene encodes the primary sigma factor of RNA polymerase and is essential for cell growth. We have mutated conserved region 2.3 of the sigma A protein to substitute each of seven aromatic amino acids with alanine. Several of these aromatic amino acids are proposed to form a melting motif which facilitates the strand separation step of initiation. Holoenzymes containing mutant sigma factors recognize promoters, but some are defective for DNA melting in vitro. We have studied the ability of each mutant sigma factor to support cell growth by gene replacement and complementation. The two region 2.3 mutants least impaired in promoter melting in vitro (Y180A and Y184A) support cell growth in single copy, although the Y184A allele imparts a slow-growth phenotype at low temperatures. A strain expressing only the Y189A variant of the sigma A protein, known to be defective in DNA melting in vitro, grows very slowly and is altered in its pattern of protein synthesis. Only the wild-type and Y180A sigma A proteins efficiently complement a temperature-sensitive allele of sigA. Overexpression of three of the sigma A proteins defective for promoter melting in vitro (Y189A, W192A, and W193A) leads to a decrease in RNA synthesis and cell death. These results indicate that mutations which specifically impair DNA melting in vitro also impair sigma function in vivo and therefore support the hypothesis that sigma plays an essential role in both DNA melting and promoter recognition.